Factor structure of preparedness of young athletes in aerobic gymnastics - Liudmila Yusupava; Inna Bodrenkova; Tetiana Moshenska (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to conduct a multifactor analysis of the training of young athletes in aerobic gymnastics, to identify the leading factors and justify the planning of the training process of athletes in this sport. Material and methods: the study involved 20 athletes aged 7-9 years. Research methods: analysis and generalization of data of scientific and methodical literature, pedagogical observation, pedagogical testing, pedagogical experiment and methods of mathematical statistics. Results: the current state of the training process of young athletes in aerobic gymnastics has been studied and the specifics of this sport have been studied. The factor structure of training of young athletes of aerobic gymnastics is determined and 6 main factors are established. It has been experimentally proved and mathematically confirmed that the first and most important factor included indicators of speed and strength training and topping test in combination with anthropometric data. The obtained data coincide with the data of correlation analysis and indicate that in modern aerobic gymnastics the accuracy of movements should be combined with speed and strength training and anthropometric data. Conclusions: the results of factor analysis showed that when teaching the basic technical elements in aerobic gymnastics should focus not only on the spatio-temporal parameters of performance, but also on the speed-power aspect of their performance.